DEVELOPMENT OF A HANDBOOK FOR THE REHABILITATION OF POST-STROKE DYSPHAGIA AND COMMUNICATION DISORD - Phan Thi Van , Huyen; Le Khanh , Dien; Vo Nguyen , Trung (Tạp chí Y Dược Thực hành 175, 2024)
Objective: Development of a handbook for the rehabilitation of post-stroke dysphagia and communication disorders. Subjects and methods: Surveying the awareness and opinions of 20 post-stroke patients’ caregivers at the Rehabilitation and Neurology department at Military Hospital 175 with self-design questionare. The handbook was written based on the Arizona State University Handbook Development and evaluated by experts before applying to the caregivers. After 1 week of use, the Patient Education Materials Assessment Tool was used to evaluate understandability, applicability and convenience by caregivers. Results: 70% of caregivers agreed that stroke leaves many serious sequelae for the patient. 55% of caregivers agreed that the sequelae post-stroke, especially the sequelae of dysphagia and/or communication disorders, greatly affect the patient, caregivers, family, and society. 80% of relatives and caregivers are having difficulty understanding dysphagia, communication disorders post-stroke, and Speech & Language Therapy for rehabilitation post-stroke dysphagia and communication disorders. 70% of caregivers have difficulty finding information. 95% of caregivers need to be provided information by the handbook for the rehabilitation of dysphagia, and communication disorders post-stroke. The handbook was completed with 43 pages, evaluated by 06 Speech and Language therapists, 01 Rehabilitation doctor, 01 Neurologist and rated by caregivers for understandability at 98.2%, applicability and convenience at 100% according to the Patient Education Materials Assessment Tool. Conclusion: Caregivers’ need for communication disorders and dysphagia knowledge is urgent and understandable. Speech and Language therapy plays an important role in the rehabilitation of post-stroke dysphagia and communication disorders. In the context of a shortage of human resources in Speech and Language Therapy, the handbook should be widely applied in the Rehabilitation deparments, Neurology departments, and nursing homes...